The impact of educational interventions for patients living with indwelling urinary catheters: A scoping review. Issue 4 (3rd July 2020) - Alex, Joby; Salamonson, Yenna; Ramjan, Lucie M.; Montayre, Jed; Fitzsimons, Jennifer; Ferguson, Caleb
Abstract : Aim : To explore the impact of educational interventions for patients living with indwelling urinary catheters. Methods : Systematic scoping review in accordance with PRISMA guidelines, guided by Cochrane methodology, quality appraisal using Centre for Evidence-Based Medicine (CEBM) Joanna Briggs Institute (JBI), GRADE criteria and Quality Improvement Minimum Quality Criteria Set Version 1.0 (QI-MQCS V 1.0) tools. Studies ( n = 446) were retrieved from CINAHL, Cochrane Library, Scopus and Medline from 2000 to 2020. Results : A total of 15 primary research studies were included in the narrative thematic synthesis, nine were from the USA, two from Australia, two from the UK, one from Italy and one from Turkey. These 15 studies were published between 2003 and 2019 and accounted for 19918 patients with an age range 15–99 years. Study design varied; there were 11 quantitative and 4 qualitative studies. Studies were of low-moderate quality. A total of four themes were identified; (i) information needs of patients living with long-term catheters; (ii) core learning content and educational approaches; (iii) feasibility and effectiveness of educational interventions to reduce complications and improve quality of life; and (iv) common outcome measures. Conclusion : The dissemination of information and the delivery of urinary catheter education to patients is inadequate. Core components of educational interventions should address fluid intake, bowel management, hygiene and self-monitoring/management, including adverse events. There is a need for future robust trials of educational and self-management interventions to improve the quality of life of patients living with indwelling urinary catheters in the community. Impact : This review addressed the educational needs of patients living with indwelling urinary catheters and the impact of educational interventions. Despite the heterogeneity in educational interventions, all studies included in this review reported the specific approach undertaken was effective in minimising catheter-associated complications and improving the quality of life of patients.